MPPT for Photovoltaic System Using Multi-objective Improved Particle Swarm Optimization Algorithm - Yuhong Zhao; Xuecheng Zhao; Yunhui Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Making full use of abundant renewable solar energy through the development of photovoltaic (PV) technology is an effective means to solve the problems such as difficulty in electricity supply and energy shortages in remote rural areas. In order to improve the electricity generating efficiency of PV cells, it is necessary to track the maximum power point of PV array, which is difficult to make under partially shaded conditions due to the odds of the appearance of two or more local maximum power points., In this paper, a control algorithm of maximum power point tracking (MPPT) based on improved particle swarm optimization (IPSO) algorithm is presented for PV systems. Firstly, the current in maximum power point is searched with the IPSO algorithm, and then the real maximum power point is tracked through controlling the output current of PV array.,. The MPPT method based on IPSO algorithm is established and simulated with Matlab / Simulink, and meanwhile, the comparison between IPSO MPPT algorithm and traditional MPPT algorithm is also performed in this paper. It is proved through simulation and experimental results that the IPSO algorithm has good performances and very fast response even to partial shaded PV modules, , which ensures the stability of PV system. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3965